Zgodovina raziskovanja tekočih kristalov - Južnič, Stanislav (Vakuumist, 2001)
We researched the discovery, later development, and the contemporary use of the liquid crystals in technology. We are publishing the very first among the researchers of the topics that finds the genesis of the modern ideas in the past centuries. To find the origins of the liquid crystals concept we studied the Jesuit prints and manuscripts inCollegio Romano and in the college of Ljubljana, especially in their relation to the interpretation of the Arsitotelian and other concepts and other concepts of matter and its spedies up to the later Boscovich's physics. A time development of the theories of matter in the Jesuit manuscripts and prints were used to illustrate the development of concepts of matter in Jesuit schools of Italz and Ljubljana. Wedescribed how they evolved from peripatetic concepts of earth, water, air (and fire), through the Cartesina snow-flake crystals, Boyle's chemical concepts of matte, and Gassendi's atomic theory in the mid 17th century, to the Boscovich's views in the second part of the 18th century. We tried to showhow Jesuit and other concepts of the 18th century infulenced the changing of the concepts of matter in the next century, especially in connections with the intermediate states of matter expressed in the discovery o the liquid crystals. We described the idea of the intermediate states between liquid and solid as an extesnsion of the former Boscovich's idea of the general continuity in nature. In that as in other cases Boscovich's general theory wasextended to the areas he didn't thing about, sometimes in Great Britain also contrary to Boscovich's original worldview. The Boscovich influence was traced at the development of the early crystallography to the separate branch of sciencein the first half of the 19th century. The Boscovich continuity ideas finally became very influential in the biological and physiological research of the group around the Berlin physical society which published the first description of the (lyotropic) liquid crystals in the mid 19th century.
Keywords: crystallography; kristalografija; tekoči kristali; zgodovinski pregledi